Global Effects of Early Life Stress on Neurons and Glial Cells - Zulma, Duenas; Carlos, Caicedo-Mera J.; Luz, Torner (Current Pharmaceutical Design, 2017)
Early life stress is considered a risk factor for the development of many diseases in both adolescence and adulthood. It has been reported that chronic stress (for instance, due to maternal separation during breast feeding), causes damage to the central nervous system at the level of neurons and glial cells, which are reflected in behavioral disturbances and susceptibility to the development of primarily emotional psychopathology. The aim of this review is to identify the overall state of the scientific literature that relates the information about the consequences of early life stress, contextualizing the mechanisms that may be altered, the behavioral consequences that have been studied and the possible dimorphic effects and its causes. At the end a short overview of pharmacological treatments that have been proposed to reduce the behavioral and neuroendocrine consequences caused by early life stress is presented. This review pretends to integrate general but relevant information based primarily on studies in animal models, which allow the experimental approach and the study of the mechanisms involved. A series of questions remains for reflection and surely will be answered in the near future.
Keywords: chronic stress